PENERAPAN TERAPI BERMAIN PLASTISIN (PLAYDOUGH) TERHADAP TINGKAT KECEMASAN AKIBAT HOSPITALISASI PADA ANAK USIA PRASEKOLAH (3-6 TAHUN) DENGAN DEMAM THYPOID DI RUANG MELATI RUMAH SAKIT TK. II DUSTIRA CIMAHI - Tifa Putri Gunasyah, Dewi; Aziz, Abdul; Taufik Ismail, Iqbal (Jurnal Kesehatan An-Nuur, 2024)
Typhoid fever is an acute infectious disease caused by Salmonella thyphi bacteria, which symptomatically affects the digestive tract. Severe typhoid fever resulted in the child being hospitalized. Preschool-aged children who are undergoing hospitalization tend to experience fear and anxiety when nursing procedures are carried out. Anxiety in children can be treated with various methods and media, one of which is plasticine play therapy. This study aims to identify the application before and after plasticine play therapy in children with typhoid fever. The research method used is descriptive-analytic with a case study approach, utilizing the nursing process, which starts with an assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. The instruments used in the research were nursing care, observation sheets, CEMS (children's emotional manifestation scale), standard operating procedures (SOP) for plasticine play therapy, and 1 set of plasticine. Data collection was carried out on one subject, a four-year-old child with a diagnosis of typhoid fever. The intervention was given once a day for three days with a duration of 30 minutes. The research results showed that there was a decrease in anxiety levels from a score of 19 (moderate anxiety) to a score of 8 (no anxiety). The impact of implementing plasticine play therapy can reduce anxiety because the child's attention can be distracted from anxiety, fulfil the child's emotional needs, and help the child's socialization process.